A selection of Belgian Works of Art : 1870-1970 - Seynaeve, Danielle; de Schaetzen, Christine; Galerie Patrick Derom, Brussels (Brussel : Galerie Patrick Derom, 1993)
Meunier, Constantin ; Van Rysselberghe, Théo ; Meunier, Constantin ; Evenepoel, Henri ; Rops, Félicien ; Khnopff, Fernand ; Minne, George ; Rousseau, Victor ; etc.
A Selection of Belgian Works of Art : 1870-1970, Galerie Patrick Derom, Brussel, Autumn 1993
boek